Pengaruh Pengembangan Karir, Keterlibatan Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Pada Puri Raja Hotel Kabupaten Badung - Ni Kadek Putri Yuniasari; Sapta Rini Widyawati; Ni Putu Ayu Sintya Saraswati (Jurnal Ekonomi dan Bisnis Digital, 2024)
This research was conducted at the Puri Raja Hotel in Badung Regency, and focused on the influence of career development, work involvement, and workload on employee performance. This research involved a population and sample of 47 employees of the Puri Raja Hotel in Badung Regency. Observations, interviews, and questionnaires were used to collect data. Data were analyzed using validity, reliability, classical assumptions, multiple linear regression analysis, multiple correlation, coefficient of determination, and t test. All of these tests were carried out using the SPSS version 26 program. The research results showed that workload had a negative and significant impact on employee performance, while work engagement and career development had a positive and significant impact on employee performance.